The World treasury of children$1 (Bs literature s - Fadiman, Clifton, 1904-1999.; Morrill, Leslie H. (Boston : Little, Brown, 1984)
A three-volume anthology of classical and contemporary children$1 (Bs stories, poems, myths, and legends from many countries.s
Includes indexes.
Keywords: Children$1 (Bs literature.s; Literature -- Collections